Absolute nucleated red blood cells counts do not predict the development of bronchopulmonary dysplasia. (18th May 2016) - Marom, Ronella; Mimouni, Francis B.; Lubetzky, Ronit; Deutsch, Varda; Mandel, Dror
Abstract: Objective : We tested the hypothesis that infants with bronchopulmonary dysplasia (BPD) have higher absolute nucleated red blood cells (aNRBCs) counts at birth than controls as a proxy measurement of exposure to intrauterine hypoxia. Methods : We studied 39 preterm infants with BPD and compared them to 39 pair-matched controls without BPD. Criteria for exclusion in both groups included factors that may influence the aNRBCs at birth. Results : In logistic regression, when pre-eclampsia, birthweight, gender, antenatal steroid therapy, 1-min Apgar scores, respiratory distress syndrome (RDS) (or surfactant use), intraventricular hemorrhage of grade 3 or more, nosocomial sepsis, patent ductus arteriosus, and aNRBC counts (or lymphocyte counts) were used as independent variables, and BPD as the dependent variable, only RDS (or its proxy measurement of surfactant use) and nosocomial sepsis remained included in the final analysis. Conclusions : aNRBC counts and lymphocyte counts do not appear to be elevated in infants that develop BPD, as compared to pair-matched controls without BPD. We speculate that chronic intrauterine hypoxia does not appear to play a major role in the pathogenesis of BPD. In contrast, postnatal events such as RDS and nosocomial sepsis appear to play a determining role in the pathogenesis of BPD.